2′-(R)-Fluorinated mC, hmC, fC and caC triphosphates are substrates for DNA polymerases and TET-enzymes. Issue 100 (1st December 2016) - Schröder, A. S.; Parsa, E.; Iwan, K.; Traube, F. R.; Wallner, M.; Serdjukow, S.; Carell, T.
Abstract : A deeper investigation of the chemistry that occurs on the newly discovered epigenetic DNA bases 5-hydroxymethyl-(hmdC), 5-formyl-(fdC), and 5-carboxy-deoxycytidine (cadC) requires chemical tool compounds, which are able to dissect the different potential reaction pathways in cells. Abstract : A deeper investigation of the chemistry that occurs on the newly discovered epigenetic DNA bases 5-hydroxymethyl-(hmdC), 5-formyl-(fdC), and 5-carboxy-deoxycytidine (cadC) requires chemical tool compounds, which are able to dissect the different potential reaction pathways in cells. Here we report that the 2′-( R )-fluorinated derivatives F-hmdC, F-fdC, and F-cadC, which are resistant to removal by base excision repair, are good substrates for DNA polymerases and TET enzymes. This result shows that the fluorinated compounds are ideal tool substances to investigate potential C–C-bond cleaving reactions in the context of active demethylation.